PENGARUH KONSENTRASI NaOH DAN GLISEROL TERHADAP KARAKTERISTIK BIOPLASTIK BERBASIS SELULOSA DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) EFFECT OF NaOH AND GLYCEROL CONCENTRATIONS ON THE CHARACTERISTICS OF CELLULOSE-BASED BIOPLASTICS FROM FRAGRANT PANDAN LEAVES (Pandanus amaryllifolius Roxb.) - Islami, Zuyyina Isnaini; -, Zulferiyenni; -, Susilawati; Hidayati, Sri; Utomo, Tanto Pratondo; Nur, Muhammad (Jurusan Teknologi Hasil Pertanian, 2024)
Fragrant pandan leaves have the potential to be used as biodegradable bioplastics that can be broken down by microorganisms in the soil. Fragrant pandan leaves contain a relatively high amount of cellulose, specifically 48.79%. This study aims to determine the effect of NaOH and glycerol concentrations on the characteristics of cellulose-based bioplastics made from fragrant pandan leaves, as well as to investigate the interaction effects between NaOH and glycerol on these bioplastic characteristics. This research arranged by using Design Random Group Complete (RAKL) with two factors and three replications. The first factor is the NaOH concentration, coded as (N), which includes three concentrations (2.5%, 5%, and 7.5%) (b/v). The second factor is the glycerol concentration, coded as (G), with three concentrations (0.5%, 1%, and 1.5%) (b/v). The research results indicate different effects on the characteristics of cellulose-based bioplastics from pandan leaves. All characteristics, except for the percentage elongation value of the produced bioplastics, met JIS 1975 standards, were degradable within 7 days, and had room temperature resistance for 2 weeks.